Guía para elaborar un BCP en entidades del estado (2016)
The purpose of this document is to describe a methodology to create the business continuity plan for the information technologies in the state entities; updating and complementing the "Guía para la preparación de las TIC para la continuidad de Negocio", which is part of Security Model and the Information Privacy emitted by the Information Technology and Communications Ministry (MINTIC), in the version 3.0 of march 2015; taking as base of reference the frameworkfor Security of MINTIC, Cobit 5.0 and it process DSS04 Continuity Management, and ISO 22301 and ISO 27001: 2013.